Differential parasitism by four species of phorid flies when attacking three worker castes of the leaf-cutting ant Atta laevigata (Smith, 1858). - Maria Lucimar O Souza; Rafael J Oliveira; Danival J Souza; Richard I Samuels; Marcos A L Bragança (PLoS ONE)
Certain species of parasitic flies belonging to the Phoridae are known to attack Atta spp. workers foraging along trails, near nest openings used by the ants to supply the colony with plant material, and in the areas where the ants are actively cutting plant material. However, there have been no previous studies of phorid parasitism of non-foraging worker ants, for example excavators and soldiers. Excavators can be found on the surface around specialized nest openings, carrying and dumping soil on characteristic mounds. Soldiers can be found on the trails protecting foragers or guarding the different types of nest openings. The current study was performed to investigate the differential parasitism rates of Atta laevigata (Smith, 1858) worker castes by four species of phorids. Ants of all castes on trails and at nest entrances were collect from 18 mature colonies in the field. A total of 21,254 ants were collected from trails and 14,649 collected from the mounds of loose soil near nest openings. The captured workers were maintained under controlled laboratory conditions to evaluate the rate of parasitism. Of the ants collected from trails, 1,112 (5.23%) were found to have been parasitized, of which 1,102 were foragers and only 10 were soldiers. Of the ants collected from the soil mounds near the nest openings, only 27 (0.18%) were found to have been parasitized, of those 25 were excavators and 2 were soldiers. When evaluating parasitism of ants on the trails, 46.2% were attacked by Apocephalus attophilus Borgmeier, 1928, 22.6% by Myrmosicarius grandicornis Borgmeier, 1928, 16.6% by Eibesfeldtphora erthali (Brown, 2001) and 14.6% by Apocephalus vicosae Disney, 2000. Only two species of phorid, M. grandicornis and E. erthali, were observed parasitizing excavators, whilst only E. erthali parasitized soldiers. This is the first time that Atta spp. excavators and soldiers have been shown to be parasitized by phorids. The low rates of parasitism and specificity of certain phorid species for excavators and soldiers is discussed in relation to the behavioral interactions of hosts and their parasitoids, as well as the relationship between host and parasitoid size.